Improving Socio-economic Efficiency of Ho Chi Minh City’s FDI Enterprises Towards Sustainable Development - Duc Hoang Tho, Nguyen (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
Ho Chi Minh City (HCMC) is known as the economic leader of Vietnam. This city also makes a major contribution to Vietnam’s state budget revenue. The reality of the socio-economic development of HCMC reveals that the Foreign Direct Investment (FDI) sector has made important and effective contributions in terms of exports, state budget revenue, job creation and income. However, the investment efficiency of this sector and technology transfer through FDI has not been as high as expected. Using secondary data, this article analyzes and assesses the socio-economic efficiency of the FDI sector in HCMC according to some criteria, namely: investment efficiency, export, state budget revenue, technology transfer, job creation and income generation. On that basis, some policy recommendations are proposed to improve the socio-economic efficiency of the FDI sector in HCMC in the direction of sustainable development, including: (i) enhancing to attract and use FDI consistently with the socio-economic development strategy of HCMC; (ii) continuing to formulate and complete investment incentive policies and tax policies; (iii) improving the effectiveness and efficiency of state management and (iv) developing human resources, science and technology to create necessary prerequisites for absorbing positive spillover effects, as well as limiting the negative impact of FDI inflows.